Activation of human C-Fibers by Lysophosphatidic Acid - Düll, Miriam; Stengel, M.; Wurm, L.; Ries, V.; Kremer, Andreas; Namer, Barbara (2017)
EVALuna2:33350

Activation of human C-fibres by lysophosphatidic acid - Düll, Miriam; Stengel, M.; Wurm, L.; Ries, V.; Kremer, Andreas; Namer, Barbara (2017)
EVALuna2:33347

Chronic pruritus represents a major burden in non-cholestatic hepatobiliary disorders - Düll, Miriam; Karlen, Vanessa; Vetter, Marcel; Dietrich, Peter; Kupfer, Joerg; Neurath, Markus; Kremer, Andreas (JOURNAL OF HEPATOLOGY, 2022)
CRIS-Team WoS Importer:2022-08-12

Empfohlene Diagnostik bei Pruritus auf primär unveränderter Haut - Düll, Miriam; Kremer, Andreas (Die Dermatologie, 2024)
Background: Chronic pruritus affecting primary non-lesional skin (CPNL) manifests as a common symptom across a spectrum of diseases spanning various medical specialties. Given the diverse etiological factors involved, diagnosing the underlying condition poses a significant challenge. Objectives: To provide a comprehensive overview of clinical, laboratory, and imaging diagnostics for CPNL. Materials and methods: A thorough literature search on the diagnostics of chronic pruritus was conducted using PubMed with specific keywords “chronic pruritus AND non-lesional skin”, “chronic itch AND non-lesional skin”, “chronic pruritus AND diagnostics”, “chronic itch AND diagnostics”, “CKD-aP”, “hepatic pruritus”, “cholestatic pruritus”, and “myeloproliferative neoplasms AND pruritus”. Results: A systematic diagnostic approach is recommended for patients with CPNL, guided by the prevalence of pruritus-associated diseases. Initial basic diagnostics facilitate a cost-effective and focused evaluation during the initial medical assessment. Information pertaining to underlying diseases can be further refined through specialized diagnostic procedures. Conclusions: CPNL often presents a diagnostic dilemma. Adopting a stepwise diagnostic strategy facilitates the identification of underlying etiologies, which is crucial for recognizing diseases and administering pruritus-specific pharmacotherapy.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Basic diagnostic workup; Itch; Liver; Myeloproliferative neoplasms; Stepwise diagnostic strategy

Endogenous Opioid Levels Do Not Correlate With Itch Intensity and Therapeutic Interventions in Hepatic Pruritus - Düll, Miriam; Wolf, Katharina; Vetter, Marcel; Dietrich, Peter; Neurath, Markus; Kremer, Andreas (Frontiers in Medicine, 2021)
Background: Chronic pruritus affects up to 70% of patients with immune-mediated hepatobiliary disorders. Antagonists of the μ-opioid receptor (MOR) and agonists of the κ-opioid receptor (KOR) are used to treat hepatic itch, albeit with limited success. An imbalance between ligands of MOR and KOR receptors has recently been suggested as a potential mechanism of hepatic pruritus. In this study, we therefore investigated systemic levels of important endogenous opioids such as β-endorphin, dynorphin A, Leu- and Met-enkephalin in plasma of a large cohort of well-characterized patients with immune-mediated cholestatic disorders, including patients with liver cirrhosis, and during effective anti-pruritic therapy. Methods: Plasma samples and clinical data were prospectively collected from well-characterized patients with primary/secondary sclerosing cholangitis (PSC/SSC), primary biliary cholangitis (PBC) and overlap syndromes suffering from pruritus (n = 29) and age-, gender- and disease-matched controls without pruritus (n = 27) as well as healthy controls (n = 20). General laboratory testing for hepatobiliary and renal function was performed. Levels of β-endorphin, dynorphin A, Leu- and Met-enkephalin were quantified in plasma by ELISA. Intensity of pruritus over the last week was evaluated using a visual analog scale (VAS, 0–10). Results: PBC and PSC patients with or without pruritus did neither differ in disease entity, disease stage, nor in the presence of cirrhosis. While both dynorphin A and β-endorphin concentrations were lower in pruritic patients compared to those without pruritus and healthy controls, the MOR/KOR ligand ratio was unaltered. No significant differences were observed for Leu- and Met-enkephalin concentrations. Opioid levels correlated with neither itch intensity nor stage of disease. Cirrhotic patients displayed higher concentrations of MOR agonist Leu-enkephalin and KOR agonist dynorphin A. Endogenous opioid levels remained largely unchanged after successful treatment with the potent anti-pruritic drugs rifampicin and bezafibrate. Conclusions: Endogenous opioid levels and the MOR/KOR ligand ratio neither correlate with itch intensity nor differentiate pruritic from non-pruritic patients with immune-mediated liver diseases. Thus, endogenous opioids may modulate signaling pathways involved in hepatic pruritus, but are unlikely to represent the major pruritogens in liver disease.
CRIS-Team Scopus Importer:2021-05-14
Keywords: bezafibrate; cholestasis; dynorphin; endorphin; enkephalin; liver; rifampicin; therapy

Erratum: Correction to: Peripheral signaling pathways contributing to non-histaminergic itch in humans (Journal of translational medicine (2023) 21 1 DOI: 10.1186/s12967-023-04698-z) - Fiebig, Andrea; Leibl, Victoria; Oostendorf, David; Lukaschek, Saskia; Frömbgen, Jens; Masoudi, Maral; Kremer, Andreas E.; Strupf, Marion; Reeh, Peter; Düll, Miriam; Namer, Barbara (Journal of Translational Medicine, 2025)
CRIS-Team Scopus Importer:2025-01-31

Evaluation and Management of Pruritus in Primary Biliary Cholangitis - Düll, Miriam; Kremer, Andreas E. (CLIN LIVER DIS, 2022)
CRIS-Team Scopus Importer:2022-11-04
Keywords: Bezafibrate; Gabapentinoids; IBAT; Opioid receptors; Therapy; UVB

Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD

Integrin αVβ6: Autoantigen and Driver of Epithelial Remodeling in Colon and Bile Ducts in Primary Sclerosing Cholangitis and Inflammatory Bowel Disease. - Roth, Dominik; Düll, Miriam; Horst, Ludwig J.; Lindemann, Aylin; Malzer, Xenia; Koop, Kristina; Zundler, Sebastian; Vetter, Marcel; Jefremow, André; Atreya, Raja; Geppert, Carol-Immanuel; Weidemann, Sören; et al. (Journal of Crohns & Colitis, 2025)
BACKGROUND: Recently, autoantibodies directed against the epithelial adhesion protein integrin αVβ6 have been identified that are strongly associated with ulcerative colitis (UC). We aimed to elucidate whether anti-integrin αVβ6 (anti-αVβ6) is present in primary sclerosing cholangitis (PSC), its associated inflammatory bowel disease, or other cholestatic liver diseases and their persistence after proctocolectomy. METHODS: We detected anti-αVβ6 by an enzyme-linked immunosorbent assay in sera collected at 2 German tertiary centers, including healthy controls (N = 62), UC (N = 36), Crohn's disease (CD, N = 65), PSC-inflammatory bowel diseases (IBD) (78 samples from N = 41 patients), PSC without IBD (PSC, 41 samples from N = 18 patients), primary biliary cholangitis (PBC, N = 24), autoimmune hepatitis (AIH, N = 32), secondary sclerosing cholangitis (SSC, N = 12), and metabolic dysfunction-associated steatotic liver disease (MASLD, N = 24). In addition, sera after proctocolectomy were studied (44 samples/N = 10 patients). Immunofluorescent analyses were performed in tissue samples from liver, large bile duct from surgical resections, and colon of PSC patients. RESULTS: Anti-αVβ6 occurred in 91% of UC, 17% of CD, 73% of PSC-IBD, 39% of PSC, 4% of PBC, 14% of AIH, and 0% of healthy controls, SSC, or MASLD. Integrin αVβ6 is selectively expressed in disease-associated epithelia of both bile duct and colon. Anti-αVβ6 levels correlate moderately with intestinal disease activity in PSC-IBD, but only weakly with biliary disease. CONCLUSIONS: Anti-αVβ6 frequently occurs in patients suffering from PSC, especially in PSC-IBD. Anti-αVβ6 levels positively correlate to IBD activity in PSC-IBD, but may also occur in the absence of clinically manifest IBD in PSC.
EVALuna2:578869

Intradermally applied LPA but not bile salts induce itch and pain in humans depending on the mode of application - Kremer, Andreas; Düll, Miriam; Wurm, L.; Ries, V.; Stengel, M.; Reeh, Peter; Fischer, Michael Jochen Marco; Namer, Barbara (2017)
EVALuna2:33355

Lysophosphatidic acid activates nociceptors and causes pain or itch depending on the application mode in human skin - Düll, Miriam; Stengel, Martina; Ries, Vivien; Strupf, Marion; Reeh, Peter; Kremer, Andreas; Namer, Barbara (Pain, 2022)
ABSTRACT: Lysophosphatidic acid (LPA) is involved in the pathophysiology of cholestatic pruritus and neuropathic pain. Slowly conducting peripheral afferent C-nerve fibers are crucial in the sensations of itch and pain. In animal studies, specialized neurons ("pruriceptors") have been described, expressing specific receptors, eg, from the Mas-related G-protein-coupled receptor family. Human nerve fibers involved in pain signaling ("nociceptors") can elicit itch if activated by focalized stimuli such as cowhage spicules. In this study, we scrutinized the effects of LPA in humans by 2 different application modes on the level of psychophysics and single nerve fiber recordings (microneurography). In healthy human subjects, intracutaneous LPA microinjections elicited burning pain, whereas LPA application through inactivated cowhage spicules evoked a moderate itch sensation. Lysophosphatidic acid microinjections induced heat hyperalgesia and hypersensitivity to higher electrical stimulus frequencies. Pharmacological blockade of transient receptor potential channel A1 or transient receptor potential channel vanilloid 1 reduced heat hyperalgesia, but not acute chemical pain. Microneurography revealed an application mode-dependent differential activation of mechanosensitive (CM) and mechanoinsensitive C (CMi) fibers. Lysophosphatidic acid microinjections activated a greater proportion of CMi fibers and more strongly than CM fibers; spicule application of LPA activated CM and CMi fibers to a similar extent but excited CM fibers more and CMi fibers less intensely than microinjections. In conclusion, we show for the first time in humans that LPA can cause pain as well as itch dependent on the mode of application and activates afferent human C fibers. Itch may arise from focal activation of few nerve fibers with distinct spatial contrast to unexcited surrounding afferents and a specific combination of activated fiber subclasses might contribute.
CRIS-Team Scopus Importer:2022-02-25

LYSOPHOSPHATIDIC ACID INDUCES ITCH AND PAIN IN HUMANS DEPENDING ON THE MODE OF APPLICATION - Düll, Miriam; Wurm, Lina; Ries, Vivien; Stengel, Martina; Reeh, Peter; Fischer, Michael J.; Namer, Barbara; Kremer, Andreas (2017)
EVALuna2:33336

Management of Chronic Hepatic Itch - Düll, Miriam; Kremer, Andreas (Dermatologic Clinics, 2018)
Hepatic itch remains among the most agonizing symptoms for affected patients and a major clinical challenge for physicians. Pruritus may occur in almost all liver diseases, particularly those with cholestatic features. Hepatic itch arises irrespective of the severity of the underlying liver disease or extent of cholestasis. Antihistamines are ineffective in hepatic itch. Therapeutic recommendations consist of a guideline-based stepwise approach, starting with the anion exchange resin cholestyramine, followed by rifampicin, naltrexone, and sertraline. Bezafibrate and ileal bile acid transporter inhibitors are promising future treatment options. Experimental and invasive procedures should be reserved for refractory pruritus.
EVALuna2:35154

Mas-related G protein–coupled receptor X2 and its activators in dermatologic allergies - Kühn, Helen; Kolkhir, Pavel; Babina, Magda; Düll, Miriam; Frischbutter, Stefan; Fok, Jie Shen; Jiao, Qingqing; Metz, Martin; Scheffel, Jörg; Wolf, Katharina; Kremer, Andreas; Maurer, Marcus (Journal of Allergy and Clinical Immunology, 2020)
The Mas-related G protein–coupled receptor X2 (MRGPRX2) is a multiligand receptor responding to various exogenous and endogenous stimuli. Being highly expressed on skin mast cells, MRGPRX2 triggers their degranulation and release of proinflammatory mediators, and it promotes multicellular signaling cascades, such as itch induction and transmission in sensory neurons. The expression of MRGPRX2 by skin mast cells and the levels of the MRGPRX2 agonists (eg, substance P, major basic protein, eosinophil peroxidase) are upregulated in the serum and/or skin of patients with inflammatory and pruritic skin diseases, such as chronic spontaneous urticaria or atopic dermatitis. Therefore, MRGPRX2 and its agonists might be potential biomarkers for the progression of cutaneous inflammatory diseases and the response to treatment. In addition, they may represent promising targets for prevention and treatment of signs and symptoms in patients with skin diseases or drug reactions. To assess this possibility, this review explores the role and relevance of MRGPRX2 and its activators in cutaneous inflammatory disorders and chronic pruritus.
CRIS-Team Scopus Importer:2020-10-23
Keywords: agonists; antimicrobial peptides; atopic dermatitis; chronic spontaneous urticaria; eosinophil granule proteins; itch; MRGPRX2; MRGX2; neuropeptides; pruritus; substance P

Methylglyoxal causes pain and hyperalgesia in human through C-fiber activation - Düll, Miriam; Riegel, Kathrin; Tappenbeck, Julia; Ries, Vivien; Strupf, Marion; Fleming, Thomas; Sauer, Susanne; Namer, Barbara (Pain, 2019)
The endogenous metabolite methylglyoxal (MG) accumulates in diabetic patients with neuropathic pain. Methylglyoxal could be a mediator of diabetes-induced neuropathic pain through TRPA1 activation and sensitization of the voltage-gated sodium channel subtype 1.8. In this study, we tested the algogenic and sensitizing effect of MG in healthy human subjects using intracutaneous microinjections. The involvement of C fibers was assessed through selective A-fiber nerve block, axon-reflex-erythema, and through single nerve fiber recordings in humans (microneurography). Involvement of the transduction channels TRPA1 and TRPV1 in MG-induced pain sensation was investigated with specific ion channel blockers. We showed for the first time in healthy humans that MG induces pain, axon-reflex-erythema, and long-lasting hyperalgesia through the activation of C nociceptors. Predominantly, the subclass of mechano-insensitive C fibers is activated by MG. A fibers contribute only negligibly to the burning pain sensation. Selective pharmacological blockade of TRPA1 or TRPV1 showed that TRPA1 is crucially involved in MG-induced chemical pain sensation and heat hyperalgesia. In conclusion, the actions of MG through TRPA1 activation on predominantly mechano-insensitive C fibers might be involved in spontaneously perceived pain in diabetic neuropathy and hyperalgesia as well as allodynia.
CRIS-Team Scopus Importer:2019-10-25

Microneurography for assessing mechanisms of itch signaling in humans - Düll, Miriam; Namer, Barbara (Nova Science Publisher Inc., 2023)
Microneurography (MNG) represents the only method for recording activity of single peripheral nerve fibers in awake human subjects. It objectively allows for a correlation between nerve fiber activity and subjective sensations such as itch and pain. While recent results from molecular biology and animal studies have provided great insights into the mechanisms and molecules involved in itch signaling, we still have to consider species differences and the translation to human patient conditions. Overall, this calls for aiming at more translational studies to close the gap between new findings in basic science and clinically relevant problems. MNG is an optimal tool to further examine C-nerve fibers in this context. The MNG technique contributed to the identification of histamine-sensitive mechano-insensitive C-fibers (CMi His+), which mediate the peripheral input of histaminergic itch in human. In most clinical conditions, non-histaminergic itch signaling seems to play a more important role, and contributing mechanisms are still not fully understood. MNG recordings revealed that mechano-sensitive C-fibers (CM) mediate cowhage-dependent itch as an example of nonhistaminergic itch. Recently, MNG results also contributed to the idea that different activation mechanisms are necessary for the induction of non-histaminergic itch, such as spatial contrast, population and pattern coding.
CRIS-Team Scopus Importer:2023-08-25

Newer Approaches to the Management of Pruritus in Cholestatic Liver Disease - Düll, Miriam; Kremer, Andreas (Current Hepatology Reports, 2020)
Purpose of Review: Chronic pruritus represents a burdensome symptom in cholestatic liver disease. This review recommends a stepwise therapeutic approach, alongside with providing information on epidemiology, pathophysiology, and novel drug targets. Recent Findings: Current epidemiological data emphasize chronic itch as a major symptom in immune-mediated liver diseases such as primary biliary cholangitis affecting up to 70% of patients with a significant number suffering from long-lasting and severe pruritus. κ-opioid receptor (KOR) agonists, PPAR agonists, and ileal bile acid transporter (IBAT) inhibitors are currently investigated for their anti-pruritic efficacy in clinical trials. Future therapies may target the autotaxin-lysophosphatidic acid-axis or the Mas-related GPCR MRGPRX4. Summary: Cholestatic pruritus still remains a challenging symptom for patients and physicians. Using a stepwise approach including cholestyramine, rifampicin, bezafibrate, naltrexone, and sertraline, pruritus is often adequately manageable. KOR agonists and IBAT inhibitors are currently the most promising anti-pruritic drugs for cholestatic pruritus in development.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Autotaxin; Bezafibrate; Bile salt; IBAT; Itch; Opioid; Rifampicin

OMW: Diagnostik bei Pruritus auf primär unveränderter Haut - Düll, Miriam; Kremer, Andreas (Die Dermatologie, 2024)
CRIS-Team Scopus Importer:2024-10-11

Peripheral signaling pathways contributing to non-histaminergic itch in humans - Fiebig, Andrea; Leibl, Victoria; Oostendorf, David; Lukaschek, Saskia; Frömbgen, Jens; Masoudi, Maral; Kremer, Andreas E.; Strupf, Marion; Reeh, Peter; Düll, Miriam; Namer, Barbara (Journal of Translational Medicine, 2023)
Background: Chronic itch (chronic pruritus) is a major therapeutic challenge that remains poorly understood despite the extensive recent analysis of human pruriceptors. It is unclear how the peripheral nervous system differentiates the signaling of non-histaminergic itch and pain. Methods: Here we used psychophysical analysis and microneurography (single nerve fiber recordings) in healthy human volunteers to explore the distinct signaling mechanisms of itch, using the pruritogens β-alanine, BAM 8-22 and cowhage extract. Results: The mode of application (injection or focal application using inactivated cowhage spicules) influenced the itch/pain ratio in sensations induced by BAM 8-22 and cowhage but not β-alanine. We found that sensitizing pre-injections of prostaglandin E2 increased the pain component of BAM 8-22 but not the other pruritogens. A-fibers contributed only to itch induced by β-alanine. TRPV1 and TRPA1 were necessary for itch signaling induced by all three pruritogens. In single-fiber recordings, we found that BAM 8-22 and β-alanine injection activated nearly all CM-fibers (to different extents) but not CMi-fibers, whereas cowhage extract injection activated only 56% of CM-fibers but also 25% of CMi-fibers. A “slow bursting discharge pattern” was evoked in 25% of CM-fibers by β-alanine, in 35% by BAM 8-22, but in only 10% by cowhage extract. Conclusion: Our results indicate that no labeled line exists for these pruritogens in humans. A combination of different mechanisms, specific for each pruritogen, leads to itching sensations rather than pain. Notably, non-receptor-based mechanisms such as spatial contrast or discharge pattern coding seem to be important processes. These findings will facilitate the discovery of therapeutic targets for chronic pruritus, which are unlikely to be treated effectively by single receptor blockade.
CRIS-Team Scopus Importer:2023-12-22
Keywords: BAM 8-22; Cowhage; Discharge patterns; Microneurography; Nociceptor; Pruriceptor; Single-fiber recording; Spatial contrast; β-Alanine

Spontaneous activity of specific C-nociceptor subtypes from diabetic patients and mice: Involvement of reactive dicarbonyl compounds and (sensitized) transient receptor potential channel A1 - Becker, Anna; Babes, Alexandru; Düll, Miriam; Khalil, Mohammad; Kender, Zoltan; Gröner, Jan; Namer, Barbara; Reeh, Peter; Sauer, Susanne (Journal of the Peripheral Nervous System, 2023)
Background: Diabetic metabolism causes changes of the chemical milieu including accumulation of reactive carbonyl species, for example, methylglyoxal (MGO). MGO activates chemosensitive TRPA1 on nociceptors, but the contribution to neuronal pathophysiology causing pain and hyperalgesia in diabetic neuropathy is not fully understood. Methods: We employed single-nerve-fiber recordings in type 2 diabetes patients with (spDN) and without cutaneous pain (DN) and in streptozotocin-diabetic and healthy mice. In mice, we measured Ca++ transients in cultured DRG neurons and stimulated CGRP release from hairy skin. Results: In diabetic patients, we recorded a large proportion of pathologically altered nerve C-fibers (79%). In spDN patients we found a higher percentage (72%) of spontaneously active C-nociceptors than in DN patients (15%). The proportion of spontaneous activity was highest among pathological fibers with mechanoinsensitive fiber properties which are particularly sensitive to MGO in contrast to mechanosensitive fibers. Mouse polymodal nociceptors, in contrast to purely mechanosensitive C-fibers, showed highest prevalence of TRPA1-related chemosensitivity. In diabetic mice about 37% of polymodal nociceptors developed spontaneous activity and exhibited significantly greater MGO responses, indicating sensitized TRPA1 receptors. Low-threshold mechanosensitive Aδ-fibers were vigorously activated by MGO but independently of TRPA1 activation. Interpretation: Our translational findings suggest that TRPA1-expressing C-nociceptors, which in human correspond to mechanoinsensitive and in mice to polymodal nociceptors, are especially vulnerable to develop spontaneous activity. Those two different nociceptor classes might share the functional role as dicarbonyl-sensitive chemosensors and represent the critical nociceptor population that support the development of pain and hyperalgesia in diabetic neuropathy.
CRIS-Team Scopus Importer:2023-05-19
Keywords: calcitonin gene-related peptide; cutaneous nociceptor; excitability; mechanoinsensitive C-fiber; methylglyoxal; microneurography; neuropathic pain

Treatment of Pruritus Secondary to Liver Disease - Düll, Miriam; Kremer, Andreas (Current Gastroenterology Reports, 2019)
Purpose of Review: Pruritus is a common extrahepatic symptom in various liver disorders, in particularly those with cholestatic features. This review summarizes epidemiology, pathophysiology, evidence-based therapeutic recommendations and currently investigated drugs for pruritus in hepatobiliary disorders. Recent Findings: Recent epidemiological data suggest pruritus as a common and relevant symptom in immune-mediated liver diseases, i.e., primary biliary cholangitis (PBC) with over 70% affected patients, up to 56% suffering from chronic pruritus. The better pathophysiological understanding of hepatic pruritus has led to the identification of novel therapeutic targets, addressed in drug trials using KOR agonists, PPAR agonists, and ileal bile acid transporter inhibitors. Summary: Hepatic itch remains among the most agonizing symptoms for affected patients and a clinical challenge for physicians. Therapeutic recommendations include a guideline-based stepwise approach starting with cholestyramine, followed by rifampicin, naltrexone, and sertraline. Bezafibrate and ileal bile acid transporter inhibitors represent promising future anti-pruritic treatment options.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Autotaxin; Bile salt; Cholestasis; Liver; Lysophosphatidic acid; Pruritus